Respuesta :

Answer:

[tex]b=\frac{4c-a^{2} }{3}[/tex]

Step-by-step explanation:

First: multiply both sides by 4. 4 times c is 4c and the other sides cancels out as you are doing the inverse operation of division

Then, you have [tex]4c=a^{2} +3b[/tex]

Subtract both sides by a squared

DO NOT TAKE THE SQUARE ROOT! This is because it is a squared plus 3b so you have to do the inverse of addition

From that you get [tex]4c-a^{2} =3b[/tex]

Finally, divide both sides by 3.

You get  [tex]b=\frac{4c-a^{2} }{3}[/tex]